A simple route to γ-carbolines and indolizino[7, 6-b]indoles. Issue 46 (18th November 2015) - Pilipenko, Arkady S.; Uchuskin, Maxim G.; Trushkov, Igor V.; Butin, Alexander V.
Abstract: We designed and realized for the first time an approach to indolizino[7, 6- b ]indoles. This approach is based on the Leuckart–Wallach reaction of 2-(2-oxoalkyl)indoles with formamide followed by Bischler–Napieralski cyclization producing γ-carbolines. The alkylation of 3-alkyl-γ-carbolines with phenacyl bromides followed by the treatment of the formed pyridinium salt with base produced the target aromatic tetracyclic system. Graphical abstract: